Improving Solid-State Fermentation of Monascus purpureus on Agricultural Products for Pigment Production - Pongrawee Nimnoi (2018)
In the present study, the effects of culture medium and temperature on red pigment production and mycelia growth were evaluated. The maximum red pigment production was found when Monascus purpureus CMU001 was cultivated on potato dextrose broth at 30 °C for 2 weeks. The highest amount of dry weight was achieved when cultivated on tryptone glucose yeast extract medium. Cheap agricultural products and residues were used as substrates for pigment production. Corn meal was the best substrate for pigment production (19.4 U/gds) when compared to peanut meal, coconut residue, and soybean meal. The highest pigment yield (129.63 U/gds) was found when corn meal was supplemented with 8% (w/w) glucose, followed by coconut residue (63.50 U/gds), peanut meal (52.50 U/gds), and soybean meal (22.50 U/gds). Galactose, sorbose, psicose, and mannitol were found to be good supplements next to glucose but not xylitol. Pigment was not stable at high temperature and long exposure to UV. The intensity of red pigment decayed 30.57% and 5.41% after autoclaving and pasteurization, respectively. © 2009 Springer Science + Business Media, LLC.